2008
DOI: 10.1080/10915810802513361
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the Toxicological Potential of Capsinoids: I. Single-Dose Toxicity Study and Genotoxicity Studies of CH-19 Sweet Extract

Abstract: A single-dose oral toxicity lethal-dose study was conducted to examine the toxicity of capsinoids contained in CH-19 Sweet extract. CH-19 Sweet extract was administered once by gavage to SPF (Crl:CD(SD)) Sprague-Dawley male and female rats at dose levels of 0 (vehicle), 5, 10, or 20 ml/kg of body weight (BW). The concentration of capsinoids in the CH-19 Sweet extract was 71.25 mg/ml; this resulted in administered dose levels of capsinoids of 356.25, 712.5, and 1425 mg/kg BW, respectively. The toxicity of CH-19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
28
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 11 publications
4
28
0
Order By: Relevance
“…However, in general, the results reported herein suggest the capsinoids, in the form of CH-19 Sweet extract, are relatively nontoxic when it comes to teratogenicity (or general toxicity). This is consistent with the findings of Watanabe et al (2008) who reported low single-dose acute toxicity in rats limited to transient salivation or decreased spontaneous movement immediately following gavage administration 10 ml/kg body weight (BW) and an LD 50 >20 ml/kg as CH-19 Sweet extract (>1425 mg/kg or >285 mg/kg as capsinoids or dihydrocapsiate, respectively).…”
Section: Table 13 Observations Made During Skeletal Examinations Of Fsupporting
confidence: 92%
“…However, in general, the results reported herein suggest the capsinoids, in the form of CH-19 Sweet extract, are relatively nontoxic when it comes to teratogenicity (or general toxicity). This is consistent with the findings of Watanabe et al (2008) who reported low single-dose acute toxicity in rats limited to transient salivation or decreased spontaneous movement immediately following gavage administration 10 ml/kg body weight (BW) and an LD 50 >20 ml/kg as CH-19 Sweet extract (>1425 mg/kg or >285 mg/kg as capsinoids or dihydrocapsiate, respectively).…”
Section: Table 13 Observations Made During Skeletal Examinations Of Fsupporting
confidence: 92%
“…In comparison, Watanabe et al (2008c) reported significantly higher acute oral LD 50 values for rats. In that study, CH-19 Sweet extract was administered as a single gavage dose at levels of 0 (vehicle), 5, 10, or 20 ml/kg of body weight (BW).…”
mentioning
confidence: 78%
“…Genotoxicity for CH-19 Sweet extract (Watanabe et al 2008c) and dihydrocapsiate ) are both negative.…”
Section: Malesmentioning
confidence: 94%
See 1 more Smart Citation
“…The acute oral toxicity of CH-19 Sweet extract containing capsinoids was examined following a single gavage administration to Sprague-Dawley rats (Watanabe et al 2008). At dose levels of 0 (vehicle), 5, 10, or 20 ml/kg of body weight (BW) of CH-19 Sweet extract, rats received 356.25, 712.5, and 1425 mg capsinoids/kg BW, respectively.…”
mentioning
confidence: 99%